2011
DOI: 10.3354/ab00345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of starvation on swimming performance and body condition of pre-settlement Sparus aurata larvae

Abstract: Body condition in larval fishes is an important determinant of survival in the natural environment. However, few studies correlate body condition with behavioural traits critical for survival, such as swimming performance. In the present study, we compared normally fed larvae of gilthead seabream Sparus aurata Linnaeus, 1758, at various intervals post-hatch with larvae which were starved for 1 to 3 d (for U crit ) or 2 d (for swimming endurance). Feeding treatment (fed and or unfed) had no effect on the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 53 publications
7
32
1
Order By: Relevance
“…The two families with the most groups and species examined in this study, Mugilidae and Sparidae, have only ever been studied in temperate environments (Clark et al, ; Faillettaz et al, ; Faria et al, ; Pattrick & Strydom, ). For four species of Sparidae tested in this study, results can be compared with the results of Faillettaz et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two families with the most groups and species examined in this study, Mugilidae and Sparidae, have only ever been studied in temperate environments (Clark et al, ; Faillettaz et al, ; Faria et al, ; Pattrick & Strydom, ). For four species of Sparidae tested in this study, results can be compared with the results of Faillettaz et al .…”
Section: Discussionmentioning
confidence: 99%
“…These studies have demonstrated that many species can swim well enough to compensate for the strength of local currents, confirming that locomotion during late larval stages may contribute to the dispersal and colonisation of coastal fish populations (Houde, ; Leis, ; Staaterman et al, ). Studies have also examined temperate species, although to a lesser degree and mainly using only artificially reared fish larvae (Faria et al, , , ; Koumoundouros et al, ; Pattrick & Strydom, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, RNA:DNA have been shown to decrease when fishes are exposed to various organic and inorganic chemicals, including benzophenone (sometimes used in sunscreen), ethyl acetate (used in a wide range of applications), methyl parathion (a pesticide), para-cresol (intermediate compound used in the production of many other chemicals), hexavalent chromium (byproduct of industrial processes), cadmium, mercury and mixture of chemicals (Kearns and Atchison, 1979;Barron and Aldeman, 1984 Finally, researchers have also attempted to correlate RNA:DNA ratios with behavior-related stresses. Faria et al (2011a) found that RNA:DNA ratios varied positively with critical swimming speed and suggested that better condition led to better swimming ability for Spartus aurata larvae. Faria et al (2011b) also attempted to quantify the relationship of RNA:DNA to the critical swimming speed of Senegalese sole.…”
Section: Ability Of Rna:dna To Assess Stress and Likelihood Of Mortalitymentioning
confidence: 97%
“…The response of S. aurata larvae to nursery odor cues increased along ontogeny, thus coinciding with the development of olfactory structures and increased swimming abilities (up to 19.3 cm s −1 , 20.2 body lengths s −1 , Faria et al, 2011), as proposed by the SAAB hypothesis (Teodósio et al, 2016). The absence of pre-flexion and flexion larvae response to odor cues can be due to their incapacity to swim toward the cues, to sensing incapacity, and/or because their attraction to nursery grounds develop later during the ontogeny closer to settlement.…”
Section: Response Of Sparus Aurata Larvae To Odor Cuesmentioning
confidence: 99%
“…The swimming capabilities of Sparidae increase along ontogeny (Pattrick and Strydom, 2009;Faria et al, 2011), however, swimming capabilities are limited before post-flexionfor example, up to 3-4 times lower for Pagrus aurata (Sparidae) pre-flexion larvae (Clark et al, 2005). Indeed, a developmental threshold was identified at 24 DPH, before which insufficient swimming capability disabled responsive behavior.…”
Section: Experimental Designmentioning
confidence: 99%